A high-purity Co-containing ultra-high strength steel and preparation method thereof
By optimizing chemical composition and smelting process, combined with strict impurity control and heat treatment, the existing cobalt-containing ultra-high-strength steels have been solved, and ultra-high-strength steels with high strength, excellent toughness and good corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411877144.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-04
AI Technical Summary
The existing cobalt-containing ultra-high strength steel has low purity, insufficient fracture toughness, high manufacturing cost, poor corrosion resistance, and insufficient chemical composition.
By optimizing the proportion of chemical components, including C, Co, Cr, Mo, Ni and other elements, combining vacuum induction, electroslag remelting and vacuum self-consumption remelting triple smelting processes, the impurity content is strictly controlled, solid solution and aging treatment are carried out, and the heat treatment process is optimized.
It significantly improves the tensile strength, yield strength and fracture toughness of steel, improves corrosion resistance, reduces impurity content and manufacturing costs, and achieves a comprehensive improvement in steel performance.
Smart Images

Figure CN119753525A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy preparation, and in particular to a high-purity Co-containing ultra-high strength steel and a preparation method thereof. Background Art
[0002] Ultra-high strength steel is a type of steel material with a tensile strength of more than 1500MPa or a yield strength of more than 1350MPa. Its mechanical properties are significantly better than those of traditional steels and are widely used in the fields of aviation, aerospace, ships, marine engineering and high-end engineering machinery. Through quenching and tempering heat treatment, the austenite matrix of the steel is transformed into a microstructure dominated by lath-shaped or needle-shaped martensite, thereby significantly improving its strength and toughness. In addition, this type of material also has good fracture toughness and elongation. In order to simplify the heat treatment process and further improve the performance, a large number of studies in current technology have shown that the addition of cobalt (Co) elements can effectively increase the martensitic transformation point of ultra-high strength steel, making it easier to obtain excellent mechanical properties. For example, A-100, AF1410 and 18Ni series of cobalt-containing ultra-high strength steels have been widely used in the manufacture of pressure-bearing components and high-end molds due to their excellent mechanical properties and processing adaptability.
[0003] Ultra-high strength steel is made by adding chemical elements such as C, Ni, Cr, Si, Mn, Nb, V, Mo, and Co to steel. The chemical elements are reasonably proportioned, and a large amount of martensite structure is formed by cooling after quenching. Tempering heat treatment is used to eliminate the organizational stress, so that the quenched martensite is transformed into a stable tempered martensite structure. The carbide plays a pinning role in the martensite dislocation structure, which greatly improves the strength, hardness, and plasticity. Through the design criteria and organizational requirements of the existing technology, a variety of ultra-high strength steels have been developed. Table 1 shows a high-alloy ultra-high strength steel 18Ni250 (GB / T1299-2014 grade 00Ni18Co8Mo6AlTi), and its chemical element mass percentage is shown in Table 1:
[0004] Table 1: Chemical composition (wt%)
[0005]
[0006] The steel grade 18Ni250 shown in Table 1 is a martensitic aging ultra-high strength steel. Its advantages are simple and convenient heat treatment process, aging treatment after solid solution machining, small heat treatment deformation, good processing performance and welding performance. In recent years, it has been widely used at home and abroad, and is mostly used to manufacture pressure-bearing components and high-end molds for aviation and aerospace. Disadvantages: It contains more precious metals such as Ni, Co, and Mo elements, is expensive, has large price limitations, and is difficult to be widely used. In addition, since it does not contain Cr elements, its corrosion resistance is extremely poor. Al and Ti elements in the steel are easy to form AlN and TiN, which reduces its plasticity and toughness, and the fracture toughness cannot reach a higher value. Its manufacturing process is: vacuum induction + vacuum self-consumption → fast forging machine → solid solution → rough machining → aging → finishing.
[0007] However, the performance and manufacturing process of existing cobalt-containing ultra-high strength steel still have the following problems:
[0008] Low purity and insufficient fracture toughness: Although the existing technology usually adopts vacuum induction and vacuum consumable smelting processes to reduce the impurity content, it is difficult to completely eliminate the residual amount of gas N in the steel, resulting in the formation of nitride inclusions (such as AlN, TiN). These inclusions seriously affect the purity of the steel, thereby reducing the fracture toughness and ductility.
[0009] High manufacturing cost and limited promotion: Existing ultra-high-strength steels generally contain a large amount of precious metal elements such as nickel (Ni), cobalt (Co) and molybdenum (Mo). The high cost of these elements significantly increases the smelting cost and limits the application of the material in a wider range of fields.
[0010] Poor corrosion resistance: For example, 18Ni250 steel does not contain chromium (Cr) and its corrosion resistance is obviously insufficient, which limits its application in marine environments or high-corrosion scenarios.
[0011] Insufficiently optimized chemical composition: In the existing technology, although the strength and toughness matching of steel is improved by adjusting the chemical composition, there is still a problem of high content of residual elements (such as S and P). This not only has an adverse effect on the mechanical properties of steel, but also limits the further improvement of its processing and use performance.
[0012] To address the above problems, the current research focuses on improving the purity and uniformity of steel and reducing the formation of inclusions by optimizing the matching of chemical composition. At the same time, the use of more efficient smelting and heat treatment processes can achieve a comprehensive improvement in material strength, toughness and plasticity. These improvements will promote the wider application of cobalt-containing ultra-high-strength steel in aerospace, high-end machinery manufacturing, and marine engineering. Summary of the invention
[0013] One of the technical problems to be solved by the present invention is to provide a high-purity Co-containing ultra-high strength steel to solve the problems of mismatch between strength and toughness, low fracture toughness, poor corrosion resistance and high cost existing in the prior art.
[0014] In order to overcome the defects of the above-mentioned prior art, the present invention provides a high-purity Co-containing ultra-high strength steel, whose chemical composition includes, by mass percentage, C: 0.12-0.13%, Co: 13.0-14.0%, Ni: 5.50-6.50%, Cr: 4.5-5.50%, Mo: 3.8-4.2%, Nb: 0.05-0.10%, Si: ≤0.10%, S: ≤0.001%, Mn: ≤0.10%, P: ≤0.003%, Al: ≤0.02%, Ti: ≤0.015%, H: ≤0.00005%, O: ≤0.0008%, N: ≤0.0010%, and the balance is Fe and other inevitable impurities.
[0015] Compared with the prior art, the high-purity Co-containing ultra-high-strength steel disclosed in the present application has the following advantages: optimizing the chemical composition design, improving the strength-toughness matching of the steel, and significantly improving the martensitic transformation point and tempering stability of the steel by strictly controlling the proportions of elements such as C, Co, Cr, Mo, and Ni, thereby achieving higher tensile strength and yield strength. The introduction of corrosion-resistant elements represented by Cr and Mo effectively improves the corrosion resistance of steel, while ensuring excellent plasticity and toughness levels; extremely low impurity content ensures that the purity and performance of steel are consistent. The steel of the present invention regards S, P, Al, Ti, H, O, N, etc. as impurities and strictly controls them, and their contents are far lower than traditional standards, significantly reducing non-metallic inclusions, improving fracture toughness and fatigue life, and making the strength and toughness of steel in different directions more consistent; comprehensive mechanical properties are significantly improved: this steel has high strength (tensile strength ≥ 2100MPa) while showing good plasticity (elongation ≥ 12%) and fracture toughness, far exceeding the comprehensive performance of existing 18Ni250 steel, and fully meeting the stringent requirements for material performance in the fields of aviation, aerospace and other high-end equipment manufacturing. In summary, the present invention successfully developed a high-purity Co-containing ultra-high strength steel through component optimization and purity control, which solves the problems of mismatched strength and toughness, low fracture toughness and poor corrosion resistance in the prior art, while improving the performance consistency of steel, providing a better material selection for the high-end manufacturing field.
[0016] Another technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned high-purity Co-containing ultra-high strength steel to solve the problems of insufficient purity, serious component segregation and poor strength-toughness matching of the prepared steel in the prior art.
[0017] In order to overcome the above defects of the prior art, the present invention provides a method for preparing the high-purity Co-containing ultra-high strength steel, comprising the following steps:
[0018] S1: Smelting:
[0019] S11: preparing ingredients according to the composition ratio of high-purity Co-containing ultra-high strength steel, and smelting the raw materials in a vacuum induction furnace to obtain molten steel, and then pouring the molten steel to obtain an electrode;
[0020] S12: electroslag remelting the electrode obtained in step S11 at a smelting temperature of 1550-1600° C., and slowly cooling the electrode after demoulding to obtain an electroslag ingot;
[0021] S13: performing forging heating on the electroslag ingot after the treatment in step S12, and performing a slow cooling treatment after forging;
[0022] S14: performing vacuum consumable remelting on the electroslag ingot processed in step S13 to obtain a vacuum consumable steel ingot;
[0023] S2: Forging:
[0024] S21: heating the vacuum consumable steel ingot of step S14 to 800-1000° C. for the first time and keeping the temperature for 1-4 hours, then slowly heating the temperature to 1100-1180° C. and keeping the temperature for 1-7 hours;
[0025] S22: forging the steel ingot treated in step S21 at a starting forging temperature of 950-1100° C. and a final forging temperature of 800-900° C., and slowly cooling to room temperature after forging;
[0026] S3: The steel ingot forged in step S2 is subjected to solution treatment and aging treatment in sequence to obtain high-purity Co-containing ultra-high strength steel.
[0027] Compared with the prior art, the preparation method of the high-purity Co-containing ultra-high strength steel in the present application has the following advantages: improving the purity of the steel and reducing non-metallic inclusions:
[0028] This method uses a triple process of vacuum induction melting, electroslag remelting, and vacuum consumable remelting, which effectively reduces the content of gases and impurities such as S, P, H, O, and N in steel, and significantly reduces the formation of non-metallic inclusions, thereby greatly improving the fracture toughness and fatigue properties of steel. The specific advantages include the following:
[0029] Optimize the smelting and forging processes to avoid component segregation: The preparation method of the present invention uses a combined process of electroslag remelting and vacuum consumable remelting, combined with low-speed melting and staged heating forging, to homogenize the alloy components in the steel, significantly reduce segregation and grain coarsening problems, and ensure the consistency of material properties.
[0030] Improve comprehensive mechanical properties: The preparation method of the present invention adopts segmented insulation and precise control of the start forging temperature and the final forging temperature during the forging process, which optimizes the grain structure of the steel and further improves the strength and toughness matching of the material, ultimately achieving high-strength performance of tensile strength ≥2100MPa and yield strength ≥2010MPa, while maintaining excellent plasticity (elongation ≥12%) and corrosion resistance.
[0031] Efficient solution and aging treatment to achieve optimal performance: The preparation method of the present invention further improves the stability of the martensitic structure by optimizing temperature and time control through solution treatment and aging treatment, so that the steel still has excellent ductility and fracture toughness under high strength state.
[0032] In summary, the preparation method of the present invention significantly improves the problems of low steel purity, severe segregation and poor mechanical properties in the prior art through unique composition control and preparation process, and provides high-purity Co-containing ultra-high strength steel with excellent performance and high reliability for the aerospace and high-end equipment manufacturing fields.
[0033] In a possible implementation, in step S11, the smelting temperature is 1480-1530°C, and the pouring temperature of the molten steel is 1530-1550°C.
[0034] Compared with the prior art, the above technical solution can ensure that the molten steel is completely melted by controlling the melting temperature to 1480-1530°C, while avoiding excessively high temperatures that cause the Al and Ti elements in the crucible material to be reduced to the molten steel to form unnecessary inclusions (such as AlN and TiN). This directly reduces the content of non-metallic inclusions and improves the purity of the steel. In addition, the moderate melting temperature can significantly enhance the degassing effect and reduce the content of gases such as H, O and N, thereby reducing the risk of hydrogen embrittlement and the possibility of inclusion formation in the material. Secondly, the temperature of molten steel pouring is 1530-1550°C. Controlling the molten steel pouring temperature within this range can ensure that the molten steel is poured under optimal fluidity and avoid the generation of pores and segregation during the pouring process. Too high a temperature will lead to grain coarsening, and too low a temperature may lead to incomplete pouring or segregation inside the ingot. By precisely controlling the pouring temperature, the molding quality of the steel ingot can be improved, and segregation and casting defects can be reduced. The above-mentioned melting temperature ensures that the molten steel reaches a high purity state. The pouring temperature further optimizes the pouring fluidity and solidification uniformity on the basis of maintaining the purity of the molten steel. The synergistic effect of the two reduces the occurrence of defects such as non-metallic inclusions, segregation and pores, so that the steel ultimately has higher purity and performance.
[0035] In a possible implementation, in step S12, the slag system of the electroslag remelting is CaF2:Al2O3:MgO=65:30:5, and the weight of the slag is 36-230kg, and the baking temperature of the slag is 600-1000°C, and the baking time is 3-10h.
[0036] Compared with the prior art, the above technical scheme optimizes the slag ratio so that the slag system has good viscosity and melting point, can stably wrap impurities in the molten steel and float to the slag layer, thereby significantly reducing the inclusion content in the molten steel, and the slag weight is accurately adjusted according to the ingot size and electrode parameters to ensure that there is enough slag to cover the electrode and the molten steel surface, improve the adsorption capacity of inclusions, and avoid thermal balance problems caused by excessive slag; the control of baking temperature (600-1000℃) and time (3-10h) ensures that the slag is completely degassed, removes moisture and adsorbed gas, and prevents the release of gas into the molten steel during the smelting process to form inclusions or pores.
[0037] In a possible implementation manner, in step S12, the current of the electroslag remelting is 3KA-19KA, the power is 60kw-800kw, and the arc starting time is ≥30min.
[0038] Compared with the prior art, the above technical solution ensures the stability of the slag layer and the uniformity of the molten steel through the optimization control of the current, power and arc starting time, significantly improves the adsorption and separation efficiency of non-metallic inclusions, and further improves the gas distribution and composition uniformity in the molten steel through dynamic adjustment of the current and power, combined with sufficient arc starting time, and reduces the residual harmful gases such as H, N, and O. The setting of the current and power range ensures flexible adaptation under different ingot conditions, making the production process more efficient and reliable; ultimately, the prepared electroslag ingots have higher purity and better structural uniformity, providing a high-quality raw material basis for subsequent forging and heat treatment. The high-purity Co-containing ultra-high strength steel finally obtained has excellent strength, toughness and plasticity, providing a stable and reliable material for high-end manufacturing applications.
[0039] In a possible implementation, in step S13, the forging heating conditions are:
[0040] Initial heating: Control the temperature of the electroslag ingot entering the furnace to be lower than 600℃. After loading the furnace, perform the first heating to 800℃, and the first heating time is greater than 2h, and the first insulation is performed for 1h; then perform the second heating to 1140-1210℃, the second heating time is greater than 2h, and the second insulation is performed for 2h;
[0041] Re-burning: The temperature of the electroslag ingot after the initial heating is controlled to 1120-1160℃, and then forging is carried out, and the starting forging temperature is ≥1000℃ and the final satin temperature is ≥850℃.
[0042] Compared with the prior art, the above technical solution can effectively avoid excessive temperature gradient inside the steel ingot by slowly heating to 800℃ at low temperature in the initial heating stage, reduce the internal stress accumulation caused by uneven thermal expansion during the heating process, and prevent the steel ingot from cracking or deformation in the initial heating stage. In the second heating stage, the temperature is raised to a higher range to make the steel ingot reach a uniform austenitization state, and ensure a sufficient diffusion process. In the austenitization process, the alloy elements are redistributed, the grains are refined and segregation is reduced; in the re-burning process, the austenite grain size can be optimized and the forging deformation resistance can be reduced, and the forging is carried out at above 1000℃ to ensure that the material is in the optimal thermoplastic range and reduce the cracking tendency. If the final forging temperature is controlled above 850℃, the generation of abnormal structures during grain coarsening and recrystallization can be effectively avoided.
[0043] In a possible implementation, in step S14, the conditions for the vacuum consumable remelting are: the current in the initial stage is 4.0-11.5KA, the melting rate of the steel ingot is controlled to be 2.5-6.5kg / min in the melting stage, and the feeding stage: 2.5-6.5KA.
[0044] Compared with the prior art, the above technical solution can achieve stable arc formation by controlling the current range (4.0-11.5KA) in the initial stage of vacuum consumable remelting, ensuring a smooth start of the melting process, while suppressing the phenomenon of excessively fast melting or uneven melting caused by excessive current; and the melting rate has a key influence on the uniformity of alloy composition and the discharge of impurities during the vacuum consumable remelting process. Controlling the melting rate within the range of 2.5-6.5kg / min can minimize the occurrence of segregation while ensuring production efficiency, while promoting the removal of gases (such as H, O, N); in the shrinkage feeding stage, the current is reduced, the melting rate is finely controlled, the liquid range of the molten pool and the loose defects caused by metal shrinkage during cooling are reduced. Precise control of the shrinkage feeding stage can also effectively suppress the formation of internal defects such as segregation and shrinkage cavities.
[0045] In a possible implementation, in step S21, the charging temperature of the vacuum consumable steel ingot is less than 600° C., and the heating rate of the first heating is less than 200° C. / h.
[0046] Compared with the prior art, the above technical scheme avoids thermal stress cracks caused by drastic thermal expansion of the steel ingot in the initial stage of heating by combining low charging temperature with slow heating rate, effectively protects the overall structural integrity of the steel ingot, and under uniform heating conditions, the grain growth of the steel ingot is effectively controlled, avoiding local grain coarsening, thereby improving the thermoplastic performance in the subsequent forging process; the vacuum consumable steel ingot treated by the above scheme not only has excellent organizational uniformity and hot working performance, but also effectively reduces the risk of cracks and defects that may occur during the processing process, providing a good raw material basis for the final acquisition of high-purity Co-containing ultra-high strength steel with high strength and high toughness.
[0047] In a possible implementation, in step S3, the temperature of the solution treatment is 900-1050°C, and the holding time is 2.5 mm steel rod diameter / min+60 min; the temperature of the aging treatment is 500-540°C, and the holding time is 2.5*steel rod diameter mm / min+240 min. When the above-mentioned steel ingot is in other shapes, the round rod diameter is replaced by the steel ingot thickness.
[0048] Compared with the prior art, the above technical scheme is adopted. In the solution treatment, the alloy compounds of various elements in the steel (such as carbides or nitrides) are completely dissolved into the austenite matrix through diffusion at high temperature, and the range of 900-1050°C ensures an effective solution process. The relationship between the holding time and the thickness of the steel ingot is 2.5mm / min, which ensures that the inside of the steel ingot is fully diffused and uniform, avoiding local residual precipitates caused by insufficient time. In the aging treatment, gold elements (such as molybdenum, cobalt, chromium, etc.) form fine dispersed precipitates (such as M2C type carbides), which are precipitated through the second phase. Strengthen the matrix, and the holding time is precisely set according to the steel thickness of 2.5mm / min+240min to ensure that the precipitates are fully and evenly distributed, and the quantity and size reach the optimal ratio, thereby enhancing the strength and toughness of the steel; in the above-mentioned treatment of the present invention, the solid solution treatment provides organizational purity and uniform element distribution, laying the foundation for precipitation strengthening in the aging treatment, and the aging treatment utilizes the alloy elements uniformly distributed after solid solution to further optimize the performance through the strengthening effect of the precipitated phase. The synergistic effect of the temperature and time control of the two can achieve the best match between the strength and toughness of the steel.
[0049] In a possible implementation, in step S3, the temperature of the solution treatment is 980°C, and the temperature of the aging treatment is 520°C.
[0050] Compared with the prior art, the above-mentioned technical solution adopts 980℃ as the optimal solution temperature, which can maximize the uniform distribution of alloy elements and avoid excessive grain growth. The aging temperature of 520℃ is the optimal precipitation temperature of the precipitate phase (such as M2C carbide), which can not only ensure the fine dispersed distribution of the precipitate phase, but also avoid excessive precipitation or coarsening caused by excessive temperature. Under the synergistic effect of solution treatment at 980℃ and aging treatment at 520℃, the problem of structural inhomogeneity caused by insufficient solution or insufficient aging in the prior art is solved, and the comprehensive performance optimization of high strength (tensile strength 2100MPa), high toughness (fracture toughness significantly improved), high plasticity (elongation 12%) and high purity is achieved, which is significantly better than the existing ultra-high strength steel materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 It is a curve diagram of the initial heating of the electroslag ingot in the present invention;
[0052] Figure 2 The effect diagram of nickel in steel;
[0053] Figure 3 This is a diagram showing the effect of carbon element on the hardness of high Co-Ni steel. DETAILED DESCRIPTION
[0054] First, those skilled in the art should understand that these implementations are only used to explain the technical principles of the embodiments of the present application, and are not intended to limit the protection scope of the embodiments of the present application. Those skilled in the art can make adjustments to them as needed to adapt to specific application scenarios.
[0055] The invention provides a high-purity Co-containing ultra-high strength steel, whose chemical composition includes, by mass percentage, C: 0.12-0.13%, Co: 13.0-14.0%, Ni: 5.50-6.50%, Cr: 4.5-5.50%, Mo: 3.8-4.2%, Nb: 0.05-0.10%, Si: ≤0.10%, S: ≤0.001%, Mn: ≤0.10%, P: ≤0.003%, Al: ≤0.02%, Ti: ≤0.015%, H: ≤0.00005%, O: ≤0.0008%, N: ≤0.0010%, and the balance is Fe and other inevitable impurities.
[0056] The design principle of the steel grade described in the present invention is as follows:
[0057] As a high-purity Co-containing ultra-high strength steel, extremely low residual elements and the interaction between alloy elements and the matching of addition amounts are very important.
[0058] The role of nickel in Ben Steel is reflected in the following aspects: nickel can push the chromium content of martensitic chromium stainless steel to a higher level, thus improving the corrosion resistance of the steel, thus solving the problem that martensitic chromium stainless steel loses its hardness at the cost of improving its corrosion resistance. In martensitic chromium-nickel stainless steel, nickel has the dual role of expanding the austenite phase and lowering the Ms temperature (see Figure 1 As shown), the steel will become a single-phase austenitic stainless steel and lose its quenching ability. At the same time, nickel also reduces the ferrite content, and its effect is the best among all alloying elements. Under specific carbon and chromium content conditions, this effect can enable the steel to obtain a satisfactory phase transformation effect and maximum hardness value. Nickel can also improve the hardenability of steel, and nickel can promote martensitic transformation. Along with this effect, nickel improves the mechanical properties of steel. 6-8% nickel can still make the steel have a martensitic structure in the normalized state, but the impact toughness of 5% nickel is too low. As the nickel content increases, the strength and toughness of the steel are improved. When the nickel content is higher than 8%, the strength and toughness are reduced due to the formation of a complex mixed structure of martensite and austenite. As shown Figure 2 As shown, Figure 2 For the role of nickel in steel.
[0059] The role of molybdenum in this steel is reflected in: increasing tempering stability and strengthening secondary hardening effect, while increasing the strength of steel without reducing toughness. The addition of molybdenum can improve both the strength and tempering stability of steel. This is mainly because molybdenum forms a fine close-packed cubic phase, which has extremely high stability in the case of over-aging, slows down the M23C6 carbide substitution process, and increases the tempering stability of steel. The molybdenum content in martensitic chromium-nickel stainless steel usually fluctuates in the range of 0.5-4%. Too high molybdenum will promote the formation of ferrite, which will have an adverse effect on steel. Molybdenum can also improve corrosion resistance, low-temperature mechanical properties, high-temperature strength and tempering stability.
[0060] The role of cobalt in Ben Steel is reflected in: cobalt inhibits the recovery of martensitic dislocation substructure, promotes the precipitation of fine dispersed M2C, produces solid solution strengthening, and improves the hardness and yield strength of steel. The co-addition of cobalt and nickel can reduce the secondary hardening peak temperature by 50°C, and jointly promote the dissolution of cementite and the formation of M2C. For details, see "The Development of Aviation Ultra-High Strength Steel" - edited by Li Zhi et al. - Beijing; National Defense Industry Press, 2012.5, P71.
[0061] The role of chromium in this steel is reflected in the following aspects: Chromium plays an important role in high Co-Ni steel and ultra-high strength steel. The increase of Cr content can reduce the stability of cementite in the tempered structure, promote the dissolution of cementite, and improve the toughness of steel. The increase of Cr content can accelerate the aging kinetics, promote the formation of M2C, and move the secondary hardening peak to a lower temperature. The increase of Cr content reduces the content of Mo in M2C, thereby reducing the coherent strain between carbide and martensite grain boundary. The reduction of coherent strain leads to the reduction of steel strength.
[0062] The role of carbon in this steel is reflected in: ① During austenitization, it dissolves in the austenite mass and has an interstitial solid solution strengthening effect. The level of carbon content directly determines the strength level of the steel. The effect of carbon content on the hardness of high Co-Ni steel is shown in the figure. ② During tempering, it precipitates fine and dispersed M2C-type precipitation phases with Mo and Cr, producing a strong secondary hardening effect. The increase in carbon content increases the number of twin martensite, which is not conducive to toughness. The effect of carbon on the hardness of high Co-Ni steel is shown in the figure. Figure 3 shown.
[0063] The role of niobium in Ben Steel is reflected in the following aspects: niobium is a ferrite-forming element. Adding niobium can make the carbon in the steel form a carbon-nitrogen-niobium compound, refine the steel grains, and improve the corrosion resistance.
[0064] To summarize, harmful elements P, S, Al, Ti and gases H, O, N, etc. are regarded as impurity elements and are kept as low as possible. The raw materials are selected from intermediate alloys and metal materials of Bensteel or similar steels. After vacuum induction, electroslag remelting and vacuum consumable remelting, high-purity medium-alloy ultra-high-strength steel is achieved.
[0065] The object of the present invention is to provide a high-purity Co-containing ultra-high strength steel and a method for manufacturing the same. The material reduces the content of impurity elements in the steel and improves the purity of the steel by optimizing the raw materials; improves the purity of the steel by a triple smelting process of vacuum induction, electroslag remelting, and vacuum consumable smelting; improves the strength of the steel by adjusting the chemical composition, improves the hot processing plasticity, and improves the plasticity and toughness, reduces the gas content, and greatly reduces nitride inclusions; reduces the gas content, reduces the residual element content, adjusts the chemical composition, improves the purity of the steel and optimizes the hot processing process, and improves the crack sensitivity.
[0066] The present invention also provides a method for preparing the high-purity Co-containing ultra-high strength steel, comprising the following steps:
[0067] S1: Smelting:
[0068] S11: The ingredients are prepared according to the composition ratio of high-purity Co-containing ultra-high-strength steel. The requirements for ingredients include: adding high-purity pure iron, pure iron requires S≤0.002%, P≤0.005% or refined steel smelted by electric furnace + LF+VOD+VD, and the residual elements S, P, and Al of refined steel are required to be ≤0.001%. Add high-purity metals such as molybdenum, nickel, chromium, niobium, and cobalt; check the surface of the raw materials before loading the furnace, and no rust, oil stains, or oxidation are allowed. If there is any, it must be cleaned, and the raw materials are melted in a vacuum induction furnace to obtain molten steel. After the molten steel is poured, the electrode is obtained. After the electrode is demolded, it is slowly cooled (including sand cooling, hood cooling, pit cooling, slow cooling with the furnace, etc.), polished, flattened, and then electroslag remelted. Effectively reduce the content of chemical element S in steel, and improve non-metallic inclusions to ensure the purity of steel, prepare for improving the strength and toughness of steel, and obtain electroslag ingots;
[0069] S12: electroslag remelting the electrode obtained in step S11, the melting temperature is 1550-1600° C., and the arc starter is Bengang bell or carbon steel conductive block;
[0070] S13: performing forging heating on the electroslag ingot after the treatment in step S12, and performing a slow cooling treatment after forging;
[0071] S14: performing vacuum consumable remelting on the electroslag ingot processed in step S13 to obtain a vacuum consumable steel ingot;
[0072] S2: Forging:
[0073] S21: heating the vacuum consumable steel ingot of step S14 to 800-1000° C. for the first time and keeping the temperature for 1-4 hours, then slowly heating the temperature to 1100-1180° C. and keeping the temperature for 1-7 hours;
[0074] S22: forging the steel ingot treated in step S21 at a starting forging temperature of 950-1100° C. and a final forging temperature of 800-900° C., and slowly cooling to room temperature after forging;
[0075] S3: The steel ingot forged in step S2 is subjected to solution treatment and aging treatment in sequence to obtain high-purity Co-containing ultra-high strength steel.
[0076] As a preferred solution, in step S11, the smelting temperature is 1480-1530°C. Vacuum induction furnace smelting can improve the degassing effect by increasing the molten steel level, so a good degassing effect can be achieved when slow and low-power smelting is used. During the smelting process, the vacuum degree of the refining period is required to be ≤1Pa, the refining period holding time is ≥60min, and the refining period temperature is 1520-1540°C. If the refining temperature is too low, it will not have a refining effect. If the temperature is too high, Al and Ti in the crucible will be reduced to the molten steel. After the refining period, when the gas meets the requirements, that is, O≤15ppm, N≤15ppm, and H≤1ppm, the pouring is performed with a vacuum degree of ≤1.0Pa, and the temperature of the molten steel pouring is 1530-1550°C. If the pouring temperature is too low, the molten steel solidification pouring cannot be completed; if the pouring temperature is too high, the electrode is prone to cracking.
[0077] As a preferred solution, in step S12, the slag system of the electroslag remelting is CaF2:Al2O3:MgO=65:30:5, and the weight of the slag is 36-230kg, and the baking temperature of the slag is 600-1000°C, and the baking time is 3-10h.
[0078] As a preferred solution, in step S12, the current of the electroslag remelting is 3KA-19KA, the power is 60kw-800kw; and the arc starting time is ≥30min.
[0079] As a preferred solution, in step S13, the forging heating conditions are:
[0080] like Figure 1 As shown, the first heating: the temperature of the electroslag ingot entering the furnace is controlled to be lower than 600°C, and the first heating is carried out after loading the furnace, heating to 800°C, and the first heating time is greater than 2h, and the first insulation is carried out for 1h; then the second heating is carried out, heating to 1140-1210°C, the second heating time is greater than 2h, and the second insulation is carried out for 2h;
[0081] Re-burning: The temperature of the electroslag ingot after the initial heating is controlled to 1120-1160℃, and then forging is carried out, and the starting forging temperature is ≥1000℃ and the final satin temperature is ≥850℃.
[0082] As a preferred solution, in step S14, the conditions for the vacuum consumable remelting are: the current in the initial stage is 4.0-11.5KA, the melting rate of the steel ingot is controlled to be 2.5-6.5kg / min in the melting stage, and the shrinkage feeding stage is 2.5-6.5KA.
[0083] As a preferred solution, in step S21, the charging temperature of the vacuum consumable steel ingot is less than 600°C, and the heating rate of the first heating is less than 200°C / h.
[0084] As a preferred solution, in step S3, the temperature of the solution treatment is 900-1050°C, and the holding time is 2.5 mm steel rod diameter / min+60 min; the temperature of the aging treatment is 500-540°C, and the holding time is 2.5*steel rod diameter mm / min+240 min. When the above-mentioned steel ingot is in other shapes, the round rod diameter is replaced by the steel ingot thickness, that is, when the round rod diameter or the steel ingot thickness is 10 mm, the holding time is 4+60 min and 4+240 min, and so on.
[0085] As a preferred solution, in step S3, the temperature of the solution treatment is 980°C, and the temperature of the aging treatment is 520°C.
[0086] The following provides an embodiment combined with specific data in combination with the above technical solution to further explain the present invention:
[0087] Embodiment 1:
[0088] The present embodiment provides a high-purity Co-containing ultra-high strength steel and a preparation method, wherein the high-purity Co-containing ultra-high strength steel comprises the following components in mass ratio: C: 0.125%, Co: 13.5%, Ni: 6.0%, Cr: 5.0%, Mo: 4.0%, Nb: 0.075%, Si: ≤0.10%, S: ≤0.001%, Mn: ≤0.10%, P: ≤0.003%, Al: ≤0.02%, Ti: ≤0.015%, H: ≤0.00005%, O: ≤0.0008%, N: ≤0.0010%, and the balance is Fe and other inevitable impurities.
[0089] The preparation method comprises the following steps:
[0090] S11: Vacuum Induction Melting
[0091] According to the composition ratio of the above-mentioned high-purity Co-containing ultra-high strength steel, high-purity pure iron (S≤0.002%, P≤0.005%) and high-purity metals cobalt, nickel, molybdenum, chromium and niobium are used as raw materials. Smelting is carried out in a vacuum induction furnace at a smelting temperature of 1505°C and a steel liquid pouring temperature of 1540°C to cast an electrode.
[0092] S12: Electroslag Remelting
[0093] The electrode obtained in step S11 is electroslag remelted, the slag system is CaF2:Al2O3:MgO=65:30:5, the slag weight is 60kg, the slag baking temperature is 800℃, and the baking time is 5 hours. The melting temperature is controlled to be 1570℃, the current is 10KA, the power is 400KW, the arc starting time is 40 minutes, and the electrode is slowly cooled after demoulding to obtain an electroslag ingot.
[0094] S13: Forging Heating
[0095] The electroslag ingot was controlled to enter the furnace at a temperature lower than 600°C, and was heated to 800°C for 3 hours and kept at this temperature for 1 hour. Then, it was heated to 1180°C for 3 hours and kept at this temperature for 2 hours. Then, it was re-burned, and the electroslag ingot was heated to 1140°C, kept at this temperature for 1 hour, and slowly cooled to room temperature.
[0096] S14: Vacuum consumable remelting
[0097] The electroslag ingot obtained in step S13 is used as an electrode for vacuum consumable remelting, the current in the initial stage is 8.0KA, the melting speed in the melting stage is controlled to be 4.5kg / min, and the current in the feeding stage is controlled to be 6.0KA. After smelting, a vacuum consumable steel ingot is obtained.
[0098] S2: Forging: S21: Forging Heating
[0099] The vacuum consumable steel ingot obtained in step S14 is heated, the charging temperature is less than 600°C, the temperature is slowly raised to 1000°C, and kept at this temperature for 2 hours; then the temperature is slowly raised to 1160°C, and kept at this temperature for 5 hours.
[0100] S22: Forged
[0101] The forging was carried out at an initial forging temperature of 1050°C, the final forging temperature was controlled at 850°C, and the steel was slowly cooled to room temperature after forging.
[0102] S3: Heat treatment: S31: Solution treatment
[0103] The steel material forged in step S2 is subjected to solution treatment at 980°C for 1.5 hours, followed by rapid oil cooling.
[0104] S32: Aging treatment
[0105] The solution treated steel was aged at 520°C for 4.5 hours and then air cooled.
[0106] Embodiment 2:
[0107] The present embodiment provides a high-purity Co-containing ultra-high strength steel and a preparation method thereof, wherein the high-purity Co-containing ultra-high strength steel comprises the following components in mass percentage: C: 0.12%, Co: 13.0%, Ni: 5.5%, Cr: 4.5%, Mo: 3.8%, Nb: 0.075%, Si: ≤0.10%, S: ≤0.001%, Mn: ≤0.10%, P: ≤0.003%, Al: ≤0.02%, Ti: ≤0.015%, H: ≤0.00005%, O: ≤0.0008%, N: ≤0.0010%, and the balance is Fe and other inevitable impurities.
[0108] The preparation method comprises the following steps:
[0109] S1 smelting: S11 batching and vacuum induction melting
[0110] According to the above-mentioned component ratio, high-purity raw materials are selected and smelted in a vacuum induction furnace at a smelting temperature of 1480° C. and a molten steel pouring temperature of 1530° C. to cast electrodes.
[0111] S12 electroslag remelting
[0112] The electrode is electroslag remelted, using slag material CaF2:Al2O3:MgO=65:30:5, slag material weight is 36kg, slag material baking temperature is 600℃, baking time is 3 hours, melting temperature is 1550℃, demoulding and slow cooling are performed to obtain electroslag ingot.
[0113] S13 Heat treatment before forging
[0114] The electroslag ingot was subjected to a two-stage heating treatment, with the first heating to 800°C and keeping the temperature for 2 hours; the second heating to 1140°C and keeping the temperature for 2 hours; the re-firing temperature was controlled at 1120°C, and the ingot was forged after slow cooling.
[0115] S14 Vacuum Consumable Remelting
[0116] The electroslag ingot was remelted in a vacuum consumable furnace. The current in the melting stage was 4.0KA, the melting rate was 2.5kg / min, the current in the feeding stage was controlled to 2.5KA, and it was slowly cooled to room temperature to obtain a vacuum consumable steel ingot.
[0117] S2 Forging: S21 Forging Heating
[0118] The vacuum consumable steel ingot was heated to 800°C and kept at this temperature for 4 hours, and then slowly heated to 1100°C and kept at this temperature for 7 hours.
[0119] S22 forging and cooling
[0120] The starting forging temperature was controlled at 950°C, the final forging temperature was controlled at 800°C, and the steel was slowly cooled to room temperature after forging.
[0121] S3 heat treatment: S31 solution treatment
[0122] The forged steel ingot was heated to 900°C, kept at this temperature for 2 hours and then oil cooled.
[0123] S32 Aging Treatment
[0124] The solution treated steel ingot was heated to 500°C, kept at this temperature for 5 hours and then air cooled.
[0125] Embodiment 3:
[0126] The present embodiment provides a high-purity Co-containing ultra-high strength steel and a preparation method thereof, wherein the high-purity Co-containing ultra-high strength steel comprises the following components in mass percentage: C: 0.13%, Co: 14.0%, Ni: 6.5%, Cr: 5.5%, Mo: 4.2%, Nb: 0.10%, Si: ≤0.10%, S: ≤0.001%, Mn: ≤0.10%, P: ≤0.003%, Al: ≤0.02%, Ti: ≤0.015%, H: ≤0.00005%, O: ≤0.0008%, N: ≤0.0010%, and the balance is Fe and other inevitable impurities.
[0127] The preparation method comprises the following steps:
[0128] S1 smelting: S11 batching and vacuum induction melting
[0129] According to the above-mentioned component ratio, high-purity raw materials are selected and smelted in a vacuum induction furnace at a smelting temperature of 1530°C and a molten steel pouring temperature of 1550°C to obtain electrodes by casting.
[0130] S12 electroslag remelting
[0131] The electrode is electroslag remelted, using slag material CaF2:Al2O3:MgO=65:30:5, slag material weight is 230kg, slag material baking temperature is 1000℃, baking time is 10 hours, melting temperature is 1600℃, demoulding and slow cooling are performed to obtain electroslag ingot.
[0132] S13 Heat treatment before forging
[0133] The electroslag ingot was subjected to a two-stage heating treatment, with the first heating to 800°C and keeping the temperature for 2 hours; the second heating to 1210°C and keeping the temperature for 2 hours; the re-firing temperature was controlled at 1160°C, and the ingot was forged after slow cooling.
[0134] S14 Vacuum Consumable Remelting
[0135] The electroslag ingot was remelted in a vacuum consumable furnace. The current in the melting stage was 11.5KA, the melting rate was 6.5kg / min, the current in the feeding stage was controlled to 6.5KA, and it was slowly cooled to room temperature to obtain a vacuum consumable steel ingot.
[0136] S2 Forging: S21 Forging Heating
[0137] The vacuum consumable steel ingot was heated to 1000°C and kept at this temperature for 1 hour, and then slowly heated to 1180°C and kept at this temperature for 1 hour.
[0138] S22 forging and cooling
[0139] The start forging temperature was controlled at 1100°C, the final forging temperature was controlled at 900°C, and the steel was slowly cooled to room temperature after forging.
[0140] S3 heat treatment: S31 solution treatment
[0141] The forged steel ingot was heated to 1050°C, kept at this temperature for 3 hours and then oil cooled.
[0142] S32 Aging Treatment
[0143] The solution treated steel ingot was heated to 540°C, kept at this temperature for 6 hours and then air cooled.
[0144] Comparative Example:
[0145] The comparative example is the 18Ni250 alloy in the background technology, and its composition is shown in Table 1. The other processing steps are the same as those in Example 1, except that the heat treatment process of step S3 is different, as shown in Table 2:
[0146] Table 2 Comparison of mechanical properties
[0147] Steel grade Heat treatment method <![CDATA[R m (MPa)]]> <![CDATA[Rp 0.2 MPa)]]> A% ψ% 18Ni250 820℃×1h air cooling+480℃×4h air cooling Vertical ≥1760 ≥1670 ≥8 ≥45 Steel grade of the present invention 980℃×1h oil cooling+520℃×4h air cooling Vertical ≥2100 ≥2010 ≥12 ≥56
[0148] As shown in the table above, compared with the prior art 18Ni250, the tensile strength, yield strength, elongation and cross-sectional shrinkage are much stronger than the prior art, which further proves the principle of the preparation method of the present invention:
[0149] (1) The steel raw material preparation method of the present invention reduces the S and P contents in refined steel and greatly improves the purity of the raw materials.
[0150] (2) The method of the present invention adopts a smelting process of vacuum induction + electroslag + vacuum consumable remelting. While reducing the gas content, the residual element S is also reduced, the inclusion content is greatly reduced, and the molten steel is purified again through the slag system.
[0151] (3) Compared with the existing 18Ni250, the steel of the present invention optimizes the chemical composition, greatly reduces the residual element content, and reduces the ferrite content, so that it has high strength while still having good plasticity, and has good toughness and plasticity. At the same time, the transverse and longitudinal mechanical properties tend to be consistent. The steel of the present invention adjusts the chemical composition so that it has more martensitic structure at room temperature and improves the strength.
[0152] Secondly, the steel grades of Example 1 and Example 2 of the present invention were sampled and tested at low magnification according to ASTM A604. The results are shown in Appendix 3:
[0153] Table 3 Low-power test results
[0154]
[0155] The steels of Example 1 and Example 2 of the present invention were sampled, and non-metallic inclusions were tested according to GB / T10561 and ASTM E112. The results are shown in Appendix 4:
[0156] Table 4 Non-metallic inclusions
[0157]
[0158] Tables 3 and 4 further illustrate that Table 3 reflects the results of low-power microscopic examination, indicating that there are no obvious organizational defects in Example 1 and Example 2 during the production process, and the organizational uniformity is good, which shows that the mechanical properties and service life of the steel of the present invention are effectively improved; and Table 4 shows that the purity of the steels of the two embodiments is high, and the non-metallic inclusions are properly controlled, which further proves the strength and toughness of the steel. The grain size results show that the steel of Example 1 performs slightly better, but both meet the requirements of ultra-high strength steel, and have made substantial technical progress compared to the prior art.
[0159] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "in the present embodiment", "specific example", or "some examples" etc. means that the specific features, mechanisms, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, mechanisms, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0160] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A high-purity Co-containing ultra-high strength steel, characterized in that: Its chemical composition by mass percentage includes: C: 0.12-0.13%, Co: 13.0-14.0%, Ni: 5.50-6.50%, Cr: 4.5-5.50%, Mo: 3.8-4.2%, Nb: 0.05-0.10%, Si: ≤0.10%, S: ≤0.001%, Mn: ≤0.10%, P: ≤0.003%, Al: ≤0.02%, Ti: ≤0.015%, H: ≤0.00005%, O: ≤0.0008%, N: ≤0.0010%, and the balance is Fe and other inevitable impurities.
2. A method for preparing the high-purity Co-containing ultra-high strength steel according to claim 1, characterized in that: The following steps are involved: S1: Smelting: S11: preparing ingredients according to the composition ratio of high-purity Co-containing ultra-high strength steel, and smelting the raw materials in a vacuum induction furnace to obtain molten steel, and then pouring the molten steel to obtain an electrode; S12: electroslag remelting the electrode obtained in step S11 at a smelting temperature of 1550-1600° C., and slowly cooling the electrode after demoulding to obtain an electroslag ingot; S13: performing forging heating on the electroslag ingot after the treatment in step S12, and performing a slow cooling treatment after forging; S14: performing vacuum consumable remelting on the electroslag ingot processed in step S13 to obtain a vacuum consumable steel ingot; S2: Forging: S21: heating the vacuum consumable steel ingot of step S14 to 800-1000° C. for the first time and keeping the temperature for 1-4 hours, then slowly heating the temperature to 1100-1180° C. and keeping the temperature for 1-7 hours; S22: forging the steel ingot treated in step S21 at a starting forging temperature of 950-1100° C. and a final forging temperature of 800-900° C., and slowly cooling to room temperature after forging; S3: The steel ingot forged in step S2 is subjected to solution treatment and aging treatment in sequence to obtain high-purity Co-containing ultra-high strength steel.
3. The method for preparing high-purity Co-containing ultra-high strength steel according to claim 2, characterized in that: In the step S11, the smelting temperature is 1480-1530°C, and the pouring temperature of the molten steel is 1530-1550°C.
4. The method for preparing high-purity Co-containing ultra-high strength steel according to claim 2, characterized in that: In the step S12, the slag system of the electroslag remelting is CaF2:Al2O3:MgO=65:30:5, and the weight of the slag is 36-230kg, and the baking temperature of the slag is 600-1000°C, and the baking time is 3-10h.
5. The method for preparing high-purity Co-containing ultra-high strength steel according to claim 4, characterized in that: In the step S12, the current of the electroslag remelting is 3KA-19KA, the power is 60kw-800kw, and the arc starting time is ≥30min.
6. The method for preparing high-purity Co-containing ultra-high strength steel according to claim 2, characterized in that: In step S13, the forging heating conditions are: Initial heating: Control the temperature of the electroslag ingot entering the furnace to be lower than 600℃. After loading the furnace, perform the first heating to 800℃, and the first heating time is greater than 2h, and the first insulation is performed for 1h; then perform the second heating to 1140-1210℃, the second heating time is greater than 2h, and the second insulation is performed for 2h; Re-burning: The temperature of the electroslag ingot after the initial heating is controlled to 1120-1160℃, and then forging is carried out, and the starting forging temperature is ≥1000℃ and the final satin temperature is ≥850℃.
7. The method for preparing high-purity Co-containing ultra-high strength steel according to claim 2, characterized in that: In step S14, the conditions of the vacuum consumable remelting are: the current is 4.0-11.5KA in the initial stage, the melting rate of the steel ingot is controlled to be 2.5-6.5kg / min in the melting stage, and 2.5-6.5KA in the feeding stage.
8. The method for preparing high-purity Co-containing ultra-high strength steel according to claim 2, characterized in that: In the step S21, the charging temperature of the vacuum consumable steel ingot is less than 600°C, and the heating rate of the first heating is less than 200°C / h.
9. The method for preparing high-purity Co-containing ultra-high strength steel according to claim 2, characterized in that: In step S3, the temperature of the solution treatment is 900-1050° C., and the holding time is 2.5 mm steel rod diameter / min+60 min; the temperature of the aging treatment is 500-540° C., and the holding time is 2.5*steel rod diameter mm / min+240 min.
10. The method for preparing high-purity Co-containing ultra-high strength steel according to claim 9, characterized in that: In the step S3, the temperature of the solution treatment is 980°C, and the temperature of the aging treatment is 520°C.